Parameter-Free Time Adaptivity Based on Energy Evolution for the Cahn-Hilliard Equation (Communications in Computational Physics, 2020)
It is known that large time-stepping method are useful for simulating phasefield models. In this work, an adaptive time-stepping strategy is proposed based onnumerical energy stability and equi-distribution principle. The main idea is to use theenergy variation as an indicator to update the time step, so that the resulting algorithmis free of user-defined parameters, which is different from several existing approaches.Some numerical experiments are presented to illustrate the effectiveness of the algorithms.